Analysis of Well Water Quality Status Due to Seawater Intrusion in Dapu-Dapura Village, West Kendari District, Kendari City - Rahil Syahfitrah; Safril Kasim; Ridwan Adi Surya; Muhammad Saleh Qadri (International journal of technology and education research, 2025)
This study aims to determine the status of well water quality due to seawater intrusion in Dapu-Dapura Village, West Kendari District, Kendari City. The analysis method used is the IP (Pollution Index) method with Purposive Sampling technique to analyze samples from several wells in Dapu-Dapura Village, West Kendari District, Kendari City. The parameters measured are Temperature, Total Dissolved Solids (TDS), Electrical Conductivity (DHL), Potential of Hydrogen (pH), Sodium (Na+), Chloride (Cl-), Salinity andEscherichia coli. The results of the study showed that the Pollution Index value at station I was 0.466, at station II 0.453, and at station III 0.455. Therefore, the well water quality status in Dapu-Dapura Village is, West Kendari District, Kendari Citystill included in the classification of meeting quality standards based on class 1 quality standards in Government Regulation Number 22 of 2021.